Discovery and Clinical Evaluation of MK‐8150, A Novel Nitric Oxide Donor With a Unique Mechanism of Nitric Oxide Release. Issue 9 (September 2016) - Knox, Clayton D.; de Kam, Pieter‐Jan; Azer, Karim; Wong, Peggy; Ederveen, Antwan G.; Shevell, Diane; Morabito, Christopher; Meehan, Alan G.; Liu, Wen; Reynders, Tom; Denef, Jean Francois; Mitselos, Anna; et al.
Abstract : Background: Nitric oxide donors are widely used to treat cardiovascular disease, but their major limitation is the development of tolerance, a multifactorial process to which the in vivo release of nitric oxide is thought to contribute. Here we describe the preclinical and clinical results of a translational drug development effort to create a next‐generation nitric oxide donor with improved pharmacokinetic properties and a unique mechanism of nitric oxide release through CYP3A4 metabolism that was designed to circumvent the development of tolerance. Methods and Results: Single‐ and multiple‐dose studies in telemetered dogs showed that MK‐8150 induced robust blood‐pressure lowering that was sustained over 14 days. The molecule was safe and well tolerated in humans, and single doses reduced systolic blood pressure by 5 to 20 mm Hg in hypertensive patients. Multiple‐dose studies in hypertensive patients showed that the blood‐pressure–lowering effect diminished after 10 days, and 28‐day studies showed that the hemodynamic effects were completely lost by day 28, even when the dose of MK‐8150 was increased during the dosing period. Conclusions: The novel nitric oxide donor MK‐8150 induced significant blood‐pressure lowering in dogs and humans for up to 14 days. However, despite a unique mechanism of nitric oxide release mediated by CYP3A4 metabolism, tolerance developed over 28 days, suggesting that tolerance to nitric oxide donors is multifactorial and cannot be overcome solely through altered in vivo release of nitric oxide. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT01590810 and NCT01656408.